ENGLISH LECTURERS' PERCEPTION TOWARD PROFESSIONAL DEVELOPMENT PROGRAMS - Nurhandayani Supraptiningsih; Silih Warni; Zuhad Ahmad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2020)
This study aims to explore the experiences and perceptions of lecturers on the professional development activities of lecturers in the English Language Education Study Program. This study applied a quantitative descriptive approach by using a questionnaire as an instrument to collect data. This study's subjects were the lecturers of the English Education Study Program at a private university in Jakarta. The findings indicate that the professional development activities that have been attended by the majority of English Education lecturers are research activities, both individually and in groups, conferences or seminars, and workshops or training related to courses and/or other topics related to education. The professional development activities needed by lecturers include training related to National Education Standards (60%), multicultural teaching (60%), knowledge and understanding (competence) of the subject (53%), and teaching for students with special needs ( 53%). This study also confirms that effective time management for organizing or developing professional development activities regarding teaching schedules and other administrative activities is urgently needed. That way, lecturers can still fulfill their obligations to teach, research, and do community service while still having the opportunity to develop their professionalism.